La rhétorique et l’esthétique du bonheur collectif dans la contre-poétique d’Édouard Glissant - Lamine Rhimi, Mohamed (Ponti/Ponts, 2024)
In this study, we try to show how Edouard Glissant invites his Caribbean readers to engage in edifying societal actions, by urging them to recover their historical memory and to break free from the shackles of slavery. Correlatively, the question of happiness takes a prominent place in the novelist who conceives the intermixing between oratorical genres underlying his novelistic work and cultural project mainly depending on the deliberative aim in order to highlight the eudemonic character of happiness in his fiction. This is how rhetoric and aesthetics, as means of struggle for freedom and consequently for collective happiness, proceed to the rescue of island identity. Which rescue could not be realized far from the union of the West Indians themselves, nor outside their archipelago surroundings where they are buried. From this angle, Edouard Glissant’s sublime style, articulated with the deliberative aim, is part of constructive discourse which allows the novelist to conceive not only an insular modus vivendi, but also a modus operandi for West Indians.